O fim como princípio do Homem : uma interpretação da influência da noção de movimento nos primeiros livros da ética nicomaquéia de Aristóteles - Pretti, Daniel do Valle (2012)
In this dissertation we aim to present different ways of understanding men using the relationship between being and movement in the thought of Aristotle. According to the philosopher, nature is the proper scope to investigate beings that can change.Therefore, first of all we will analyze the importance of men in the formulation of the definition of movement. With that purpose in mind, we will contrast art and nature.Consequently, we will be able to investigate the Aristotelian understanding about the best possible realization for men s life, or rather, happiness. We sustain that the notion of happiness is onto-cosmologically grounded on the close relationship between the notion of movement and the first principle that opens the Nicomachean Ethics. At last, we will analyze what it means to guide itself by reason, since we have in view the search for self-fulfillment. In other words, we will investigate how men form a moral virtue by and for a reality in change.